2015
DOI: 10.1007/s11222-015-9617-y
|View full text |Cite
|
Sign up to set email alerts
|

Point process-based Monte Carlo estimation

Abstract: This paper addresses the issue of estimating the expectation of a real-valued random variable of the form X = g(U) where g is a deterministic function and U can be a random finite-or infinite-dimensional vector. Using recent results on rare event simulation, we propose a unified framework for dealing with both probability and mean estimation for such random variables, i.e. linking algorithms such as Tootsie Pop Algorithm (TPA) or Last Particle Algorithm with nested sampling. Especially, it extends nested sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…In this section, we recall common results from [17,19,28] in the framework of [30]. Let us consider X = S(U) ∈ R a real-valued random variable with distribution µ X where S is a deterministic function (for instance the output of a computer code) and U a random finite-or infinite-dimensional vector with known distribution µ U .…”
Section: The Increasing Random Walkmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we recall common results from [17,19,28] in the framework of [30]. Let us consider X = S(U) ∈ R a real-valued random variable with distribution µ X where S is a deterministic function (for instance the output of a computer code) and U a random finite-or infinite-dimensional vector with known distribution µ U .…”
Section: The Increasing Random Walkmentioning
confidence: 99%
“…It has the smallest variance amongst all AMS [7]; especially Simonnet [28] and Guyader et al [17] showed that the random number of iterations of the algorithm follows a Poisson law when X is continuous. Moreover Walter [30], following Huber and Schott [19], brought an original insight in terms of a random walk of the real-valued random variable X = S(U) linked with a Poisson Process with parameter 1. Indeed the estimator is found to be the Minimal Variance Unbiased Estimator (MVUE) of the exponential of a parameter of a Poisson law with N iid.…”
Section: Introductionmentioning
confidence: 99%
“…and rare event simulation (Walter, 2017). The original development of the nested sampling algorithm was motivated by evidence calculation, but the MultiNest (Feroz and Hobson, 2008;Feroz et al, 2008Feroz et al, , 2013 and PolyChord (Handley et al, 2015a,b) software packages are now extensively used for parameter estimation from posterior samples (such as in DES Collaboration, 2018).…”
mentioning
confidence: 99%
“…Further to this, [52,Remark 1] shows that this estimator results in superior estimates over exp(−t/N) in terms of variance so long as p t > exp(−1). In light of this, Walter suggests using Riemann sum quadrature using these alternative values for p t as it will result in a superior NS estimator.…”
Section: Chapter Unbiased and Consistent Nested Sampling Via Sequenmentioning
confidence: 96%
“…However, this is somewhat out of place with the rest of the quadrature. Using point process theory and techniques from the literature on unbiased estimation, Walter [52] proposes an unbiased version of NS. However, this unbiasedness relies on the assumption of independent sampling, and comes with a cost of additional variance.…”
mentioning
confidence: 99%